Life, liberty, and the pursuit of Dao : ancient Chinese thought in modern American life - Crane, George T., 1957- (Chichester, West Sussex, United Kingdom : Wiley Blackwell, 2013)
This highly original work introduces the ideas and arguments of the ancient Chinese philosophies of Confucianism and Daoism to some of the most intractable social issues of modern American life, including abortion, gay marriage, and assisted suicide. Introduces the precepts of ancient Chinese philosophers to issues they could not have anticipatedRelates Daoist and Confucian ideas to problems across the arc of modern human life, from birth to deathProvides general readers with a fascinating introduction to Chinese philosophy, and its continued relevance.
Chapter 5 Marriage and FamilyConfucians on marriage and family; Daoists on marriage and family; Same-sex marriage?; Confucian and Daoist understandings of divorce; Notes; Chapter 6 Public and Political Life; Confucian leadership; Daoist leadership; The question of democracy; Notes; Chapter 7 End of Life; Confucianism on death and dying; Daoism on death and dying; Mourning; Notes; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed on September 13, 2013).
Keywords: 2000-2099; Philosophy, Confucian; Taoist philosophy; PHILOSOPHY -- Eastern; Philosophy, Confucian; Politics and government; Social conditions; Taoist philosophy; United States -- Social conditions -- 21st century; United States -- Politics and government -- 21st century; United States; Electronic books